Garvey's Choice - Grimes, Nikki (Honesdale, Pennsylvania : Wordsong, an imprint of Highlights, 2016)
Garvey's father has always wanted Garvey to be athletic, but Garvey is interested in astronomy, science fiction, reading--anything but sports. Feeling like a failure, he comforts himself with food. Garvey is kind, funny, smart, a loyal friend, and he is also obese, teased by bullies, and lonely. When his only friend encourages him to join the school chorus, Garvey's life changes.
Keywords: Obesity in adolescence -- Juvenile fiction; Bullying -- Juvenile fiction; Fathers and sons -- Juvenile fiction; Friendship -- Juvenile fiction; Novels in verse; Obesity in adolescence -- Fiction; Bullies -- Fiction; Fathers and sons -- Fiction; Friendship -- Fiction; Novels in verse